Study of gaseous velocity slip in nano-channel using molecular dynamics simulation. Issue 6 (29th July 2014) - Bao, Fubing; Mao, Zhihong; Qiu, Limin
Abstract : Purpose: – The purpose of this paper is to investigate the gas flow characteristics in near wall region and the velocity slip phenomenon on the wall in nano-channels based on the molecular dynamics simulation. Design/methodology/approach: – An external gravity force was employed to drive the flow. The density and velocity profiles across the channel, and the velocity slip on the wall were studied, considering different gas temperatures and gas-solid interaction strengths. Findings: – The simulation results demonstrate that a single layer of gas molecules is adsorbed on wall surface. The density of adsorption layer increases with the decrease of gas temperature and with increase of interaction strength. The near wall region extents several molecular diameters away from the wall. The density profile is flatter at higher temperature and the velocity profile has the traditional parabolic shape. The velocity slip on the wall increases with the increase of temperature and with decrease of interaction strength linearly. The average velocity decreases with the increase of gas-solid interaction strength. Originality/value: – This research presents gas flow characteristics in near wall region and the velocity slip phenomenon on the wall in nano-channels. Some interesting results in nano-scale channels are obtained.